OPTIMALISASI MANAJEMEN KEUANGAN ORGANISASI DENGAN PENGEMBANGAN PLANNER KEUANGAN BERBASIS MICROSOFT EXCEL - Desmayani, Ni Made Mila Rosa; Libraeni, Luh Gede Bevi; Purnama, Ni Kadek Liryana (ASOSIASI IDEBAHASA KEPRI, 2025)
The purpose of this community service program was to improve the skills of OSIS members at SMA Negeri 9 Denpasar in using Microsoft Excel for financial management. The school faced significant challenges, including limited access to technology and a lack of proficiency in Excel, which hindered the efficiency of managing student organization finances. The community service activities were designed to address these issues by providing targeted training sessions on Excel, focusing on fundamental tools, formulas, and creating financial reports. The method involved an initial assessment of the school's needs, followed by hands-on workshops and interactive quizzes to assess understanding. The outcomes indicated a marked improvement in the students' ability to manage financial data using Excel, enhancing both their administrative efficiency and digital literacy. This project not only resolved immediate operational challenges but also equipped the students with valuable skills for future academic and professional endeavors. The results highlight the importance of integrating digital skills training into educational programs, fostering greater efficiency and preparing students for the demands of the digital age.